2011
DOI: 10.3400/avd.cr.10.01025
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Arteriovenous Fistula as a Cause for Leg Ulcers: A Case Report

Abstract: An 80-year-old man presented with painful leg ulceration due to steal phenomenon from a groin arteriovenous fistula (AVF) 10 years following a coronary angiogram. The diagnosis of the AVF was confirmed by duplex examination of the groin vessels which demonstrated characteristic flow pattern in the femoral arterial and venous system. Angiography further confirmed the site of the fistulous communication and this was managed by a covered stent graft. We discuss the incidence of AVF, risk factors for its developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…In a study by Kelm et al, spontaneous closure was found to occur in one-third of iatrogenic AVF cases, and cardiac volume overload was considered highly unlikely with AVF persistence [1]. However, some authors have reported high-output cardiac failure, limb edema, and limb ischemia as late complications of iatrogenic femoral AVF [12][13][14][15]. In the present case, AVF did not disappear at six months after the onset, and AVF-associated volume load could have had deleterious effects on the cardiac function in the setting of recurrent atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Kelm et al, spontaneous closure was found to occur in one-third of iatrogenic AVF cases, and cardiac volume overload was considered highly unlikely with AVF persistence [1]. However, some authors have reported high-output cardiac failure, limb edema, and limb ischemia as late complications of iatrogenic femoral AVF [12][13][14][15]. In the present case, AVF did not disappear at six months after the onset, and AVF-associated volume load could have had deleterious effects on the cardiac function in the setting of recurrent atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…Causes of an AV fistula formation after a flap surgery may be diverse, such as congenital dispositions, traumatic causes related to free flap transfer, long-term exposure to coldness, vasospasm, and predominance of arterial supply to venous drainage [6]. As the first hypothesis, we have assumed the cause of AV fistula formation could be traumatic injury that occurred during the flap surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Although some groups have reported on acquired AVFs in the lower extremities, most cases exhibited ischemic symptoms resulting from iatrogenic injury, such as arterial puncture during coronary angiography or the insertion of a dialysis catheter. 2 , 3 ) Traumatic injury, such as blunt or penetrating trauma, can also cause AVF. 4 6 ) It can be detected in patients with increased resistance at the precapillary level because of frostbite, scleroderma, or emboli.…”
Section: Discussionmentioning
confidence: 99%